Efferent detoxification methods and evaluation of the intensive therapy efficacy in children with bacterial toxemia - M. Yu. Kurochkin; A. H. Davydova; Yu. V. Horodkova (Zaporožskij Medicinskij Žurnal)
The main problem of severe bacterial infections intensive therapy in children is toxemia, disorder of hemodynamic and oxygen transport.